Atypical median rhomboid glossitis: A case report - Nath, Priyanka; Rath, Saroj Kumar (Indian Journal of Case Reports, 2018)
Median rhomboid glossitis or glossal central papillary atrophy is characterized by an area of redness and loss of filiform papillae, situated on the dorsum of the tongue in front of the circumvallate papillae. Smoking, denture wearing, use of corticosteroid sprays or inhalers, and human immunodeficiency virus are few of the predisposing factors. Previously, this condition was believed to be a developmental defect of the tongue, caused by a failure of the tuberculum impar to be covered by the lateral processes of the tongue; however, now, it is thought to be due to chronic candidiasis. This paper presents an atypical case of rhomboid glossitis in a 4-year-old girl, discussing the clinical presentation, etiological factors, and differential diagnosis.